THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND INFANT GROWTH AND DEVELOPMENT IN THE WORKING AREA OF THE PEUDADA COMMUNITY HEALTH CENTER, BIREUEN DISTRICT - Bukhari; Machfud (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Child growth and development are influenced by internal and external factors. One of the postnatal factors is nutritional factors. Nutritional elements are a dominant influence on child growth, especially in early life until the age of 6 months. The nutrition needed by babies can be met by providing breast milk (ASI). Exclusive breastfeeding is one effort to obtain good baby growth and development because breast milk contains important nutrients needed by babies to grow. The purpose of this study was to determine the relationship between exclusive breastfeeding and infant growth and development in the Peudada Community Health Center Working Area, Bireuen Regency. The research design used in this study was cross-sectional. The population in this study were 204 mothers who had babies aged 6-12 months. The sample used in this study was accidental sampling, namely a sampling technique based on chance, the number of samples was 67 babies. This study was conducted at the Peudada Community Health Center on July 14, 2025. Data analysis used the Chi Square test . The results of the univariate test showed that the majority of exclusive breastfeeding was in the category of providing exclusive breastfeeding as many as 40 respondents (59.7%), respondents based on appropriate growth as many as 57 respondents (85.1%) and fine and gross motor development in infants showed that 42 respondents (62.7%). The bivariate results using the statistical test above obtained a p value = 0.001. This means that the p value is smaller than α (p = 0.001 <α = 0.05 ) , so it can be said that Ho is rejected and Ha is accepted or there is a significant relationship between exclusive breastfeeding and growth in infants at the Peudada Health Center, Bireuen Regency. Suggestions for mothers should dig up information from health workers, and information media that discuss exclusive breastfeeding so that infant growth and development are met according to age and avoid delays in growth and development.